Biogeographic role of the Indonesian Seaway implicated by colonization history of purpleback flying squid, Sthenoteuthis oualaniensis (Lesson, 1830), in the Indo-Pacific Ocean - He, Lijun; Xu, Shasha; Weese, David A.; Zhang, Jie; Ren, Huimin; Tang, Fenghua; Sha, Zhongli; Zhang, Jing (Frontiers in Marine Science, 2022)
As a bio]diversity hotspot, the East Indies (Coral) Triangle possesses the highest biodiversity on the earth. However, evolutionary hypotheses around this area remain controversial; e.g., center of origin, center of accumulation, and center of overlap have been supported by different species. This study aims to answer the evolutionary influence of the Indonesian Seaway on the biodiversity of the Coral Triangle by recovering the evolutionary origins of a wide-ranging ommastrephid squid (Sthenoteuthis oualaniensis) based on integrated molecular and oceanographic clues from the Indo-Pacific. Three new clades were revealed; viz., clade I from the South China Sea, clade II from the northern East Indian Ocean, and clade III from the southern East Indian Ocean. These two Indian Ocean clades formed a monophyly closely related to clade IV from the Central-Southeast Pacific. Clade VI from the central Equatorial Pacific and clade V from the northern Eastern Pacific sit in basal positions of phylogenetic trees. Ancestral Sthenoteuthis was inferred to have originated from the Atlantic Ocean and sequentially dispersed to the northern East Pacific, central Equatorial Pacific, and West Pacific through the open Panama Seaway and being transported by westward North Equatorial Current. The East Indian Ocean was likely colonized by an ancestral population of clade IV from the Southeast Pacific. Westward South Equatorial Circulation could have promoted transoceanic migration of S. oualaniensis through the wide paleo-Indonesian Seaway. Sea level regression since the Miocene and the closure of the Indonesian Seaway at 4–3 Ma were responsible for the population genetic differentiation of S. oualaniensis in the Indo-Pacific. Therefore, the Indonesian Gateway played an important role in influencing marine organisms’ migration and population differentiation through controlling and reorganizing circulations in the Indo-Pacific.